Kinetic activity of the sex chromosomes of Mormidea paupercula (Pentatomidae, Heteroptera) - Rebagliati, Pablo Javier (2010)
InMormidea paupercula (n = 6 + XY in males), the presence of a CMA3-bright band in the telomeric regions on both sexchromosomes allowed the analysis of the kinetic activity of the sex univalents and XY pseudobivalent at the first and second meioticdivisions, respectively. The separation of the sister chromatids of the sex chromosomes occurs from a pair of telomeric regions (withor without a band), with opposite telomeric regions remaining associated with each other at meiosis I; the behaviour of both sexchromosomes differs, on the X chromosome both telomeric regions are similarly active, while on the Y chromosome the telomericregion without a band is more frequently active. At the second division, the most frequent associations in the pseudobivalent occurbetween the telomeric regions of both sex chromosomes with bands or without bands. Therefore, in both meiotic divisions, the sametelomeric region on the sex chromosomes could lead the migration, in contrast to that observed usually in autosomal bivalents. Theseresults provide evidence that the sex chromosomes of Heteroptera show more than one pattern of attachment to the spindle.